Analisis Keselamatan dan Kesehatan Kerja K3 Dengan Metode Hazard Identification Risk Assesment and Risk Control (HIRRARC) dan Job Hazard Analysis - Rusmalah; Ruspendi; Nada; Wahyuningsih, Utami (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
This study aims to identify and reduce potential hazards during the fabrication process. The research utilizes the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method for risk analysis and the Job Hazard Analysis (JHA) method to identify hazardous stages. Based on the hazard identification results, the risks associated with each task are assessed based on severity and likelihood to determine the level of risk. The findings indicate the presence of 15 potential hazards across 7 types of tasks in the Sewing Line at PT. TMT Bintan, comprising 4 moderate risk hazards, 3 high risk hazards, and 8 extreme risk hazards. Recommended Risk Control measures applicable to the sewing line system include technical controls (such as equipment maintenance or upgrades, technological improvements, and installation of protective devices), administrative controls (such as the development of regulations, warnings, safer work instructions, and health checks), and the use of personal protective equipment (PPE)